Tracing Aquatic Macrophyte Development in Nansi Lake, Northern China's Largest Freshwater Lake: Plant Macrofossils From 1855 to Present - Qinghui Zhang; Yufei Wu; Liwei Yang; Zekun Li; Zonglei Li; Yuying Yang; Shiyue Chen; Enfeng Liu (Ecology and Evolution)
ABSTRACT Examining the impacts of natural and anthropogenic influences on aquatic macrophytes in shallow lakes is crucial for their effective restoration and management. However, there is a lack of direct evidence regarding past species composition or detailed and continuous evidence of recent changes in aquatic macrophyte communities. This study utilized plant macrofossil remains deposited in the sediment, combined with macrophyte surveys from 1983 to 2010, to reconstruct the historical changes in the macrophyte community over approximately 160 years in Lake Weishan, a sub‐lake of Lake Nansi located in the lower Yellow River (Huanghe River) Basin, northern China. Approximately 54.3% of the species historically recorded at the core site were identified through macro‐remains analysis, including five previously unrecorded submerged taxa (Myriophyllum verticillatum, Ranunculus trichophyllus, Chara sp., Nitella sp., and Vallisneria spinulosa) discovered during monitoring surveys. The findings revealed four major shifts in the macrophyte community: A transition from a swampy environment dominated by emergent/wetland plants (ca. 1855–1875) to an expanded water body characterized by a rapid proliferation of submerged macrophytes (ca. 1875–1910), followed by mass disappearance of macrophytes (ca. 1910–2005) and subsequent significant resurgence (after 2005). Multiple factor analysis was employed to investigate the correlation between these shifts and changes in paleolimnological indicators (invertebrates, geochemistry, and grain size), as well as documented records related to hydrology, climate changes, and human activities. The results confirmed our hypothesis that climatically and anthropogenically induced hydrological alterations were likely the primary drivers influencing macrophyte composition alteration and succession dynamics in the lake. This study highlights the potential use of plant macrofossils for reconstructing long‐term changes in macrophyte community components, abundance assessment, and ecosystem health evaluation within the lower Yellow River region. To effectively address persistent challenges such as water diversion and climate change, we propose integrating paleoecological methods into standard ecological monitoring protocols employed for water ecological quality assessment.